PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DI JAKARTA ISLAMIC INDEX - Kristian, Indah; Darma Saputra, Yudha Mahrm; Husin Umrie, Anwar (Universitas muhammadiyah palembang, 2015)
The problem formulation of this research is looking for the influence of investment decision, funding, and dividend policy, to the value of company. The aim is knowing the level of influence of investment decision, funding, and dividend policy, to the value of company. This research is an association. There is a dependent variable, that is the value of company with the indicator of PBV. Furthermore, there are three independent variables, those are the investment decision with the indicator of PER, the funding decision with the indicator of DAR, and the dividend policy with the indicator of DPR. The population of this research is all companies in Jakarta Islamic Index which 300 companies taken from year 2010 to 2015. The requirement for sample is more than five times in the list of Jakarta Islamic Index and less than five times in the list of Jakarta Islamic Index, with the technique of purposive sampling. Polling is needed as the base of analysis, whereas the technique of collecting data is documentation. The technique of analysing data is double linear. The result of this research is the investment decision has no influence significantly to the value of company with the regression coefficient value is 0,007. Next, the funding decision has a significant influence to the value of company with the coefficient 4,454. Moreover, the dividend policy has a significant influence to the value of company with the coefficient 7,023. The result of determination coefficient in this research is R² = 0,145. This means that the value movement in Jakarta Islamic Index is influenced by the funding decision and dividend policy in the level of 14,5%. However, the investment decision does not give an influence because there is no PER value which increase continuously and also several points of negative PER.